Menace of Poverty and Education on the Mental Health Outcomes of Children in Benin Metropolis - Omorogiuwa, Tracy B.E.; Ekhorutomwen, Victory (NIU Journal of Humanities; Vol 10 No 3 (2025): NIU Journal of Humanities, Vol. 10 No. 3, September 2025DO - 10.58709/niujhu.v10i3.2270, 2025)
The primary aim of the study is to examine the menace of poverty and education on the mental health outcomes of children. It equally considers the impact of socio-economic status of the parents’ education, and family environment. Ecological theoretical framework was adopted in this study. The literature established that children growing up in poverty are at a higher risk of experiencing stress, anxiety, and depression; it can retard their opportunities for rapid growth and development; and the lack of access to basic necessities and opportunity for education and personal development can further exacerbate mental health issues among children. The research design that was adopted in this study was the phenomenological research design and a qualitative methodology. A purposive sampling technique was employed, and 10 participants were recruited for this research study. Data was gathered through interviews and was thematically analysed. The study revealed inability of the parents to take care of their wards/children’s basic needs, pushed the parents to engage them in child labour to augment income in their families and such labour increased their vulnerability and negatively impacted their overall quality of wellbeing. Similarly, it was also noted well-trained teachers are paramount to be able to manage children mental health issues.  The study recommends the implementation of policies and programs aimed at enhancing the socio-economic conditions of families in Benin Metropolis. These initiatives could include providing financial aid, creating job opportunities for parents, offering educational support for children. Keywords: Children, Education, Poverty, Mental health, Benin Metropolis